Stammzellforschung Aktuelle wissenschaftliche und gesellschaftliche Entwicklungen - Schickl, Hannah (Nomos Verlagsgesellschaft mbH & Co. KG, 2018)
Patients have high expectations of stem cells in the treatment of severe and devastating diseases that have no effective therapy at the moment. But what are stem cells? How far has stem cell research progressed internationally and, in particular, in Germany? And what is allowed or prohibited according to German law compared to other countries?